2021
DOI: 10.1142/s0219686721500104
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Bending of a Polyamide Tube Using High-Power Ultrasound

Abstract: Ultrasonic tube forming is an innovative and promising technology that could replace the conventional thermoforming process for plastic automotive tubes. This process allows for the forming of extruded tubes four times faster, with a substantial increase in energy efficiency. This research focuses on the experimental study of this innovative process and its comparison to the conventional thermoforming in a hot air table. A prototype has been designed and assembled to study the main process variables that are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Additionally, Silveira et al [20] demonstrated the applicability of the constructal law in evaluating the mechanical geometry of materials engineering systems. Montes [21] focused on the experimental study on the bending of a polyamide tube using high-power ultrasound. Shi et al [22] found that the fracture of steel wires leads to the failure of the tube, and higher temperature has a negative effect on the tubes' bending capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Silveira et al [20] demonstrated the applicability of the constructal law in evaluating the mechanical geometry of materials engineering systems. Montes [21] focused on the experimental study on the bending of a polyamide tube using high-power ultrasound. Shi et al [22] found that the fracture of steel wires leads to the failure of the tube, and higher temperature has a negative effect on the tubes' bending capacity.…”
Section: Introductionmentioning
confidence: 99%